Business with the Internet - Rumiantseva S. V. (Science and education: future development, 2019)
the article discusses the use of Internet technologies by small and medium-sized enterprises as well as natural and state monopolies in modern society. Salient features of a new type of economy are defined.
Keywords: электронная коммерция; электронная подпись; цифровые технологии; интернет-торговля; поисковая оптимизация; electronic commerce; digital signature; онлайн-технологии; бизнес-модели; digital technologies; business models; электронная торговая платформа; electronic digital signature; client – Internet market; electronic trading platform; SEO optimization; online technologies